Simultaneous Reconstruction of Mandibular and Maxillary Defects Using the Single Free Fibular Osseocutaneous Flap: Case Series and Review of the Literature. Issue 4 (April 2021) - Lin, Chih-Hung; Kudva, Adarsh
Abstract : Background: The facial profile requires adequate maxillary and mandibular projection. Although oral cancer tumor ablation might create ipsilateral maxillary and mandibular defect, fibular flap is popular in mandibular defect reconstruction. However, the maxillary defect results in sunken cheek or oral contracture. A single fibular flap can provide several struts to rebuild 2 jaws with adequate 3-dimensional spatial placement. Materials and Methods: In total, 7 cases of secondary oral contracture and 2 cases of primary oncologic tumor ablation underwent single fibular flap for 2 jaws. Using multiple osteotomies, the distal fibular struts were used for the upper jaw, the second struts were discarded (3–4 cm), and proximal struts were used for mandible defect reconstruction. There were 5 accompanying free flaps for facial lining (2) and contralateral oral contracture release (3). Results: All flaps survived without distal strut avascular necrosis, but 2 patients died from tumor metastasis. These patients presented adequate middle and lower facial profile. One patient underwent mandibular fibula strut distraction osteogenesis followed by integrated teeth on both jaws. Conclusions: Single fibular transfer can accomplish 2 jaw bony defects and facial profile reconstruction. It can release oral contracture functionally and correct sunken cheek aesthetically. The reconstructed fibula can allow secondary teeth implantation rehabilitation.